Quenched solid density functional theory and pore size analysis of micro-mesoporous carbons. - Neimark, Alexander V.; Lin, Yangzheng; Ravikovitch, Peter I.; Thommes, Matthias (Carbon, 2009)
We present a new model of adsorption on micro-mesoporous carbons based on the quenched solid d. functional theory (QSDFT). QSDFT quant. accounts for the surface geometrical inhomogeneity in terms of the roughness parameter. We developed the QSDFT models for pore size distribution calcns. in the range of pore widths from 0.4 to 35 nm from N at 77.4 K and Ar at 87.3 K adsorption isotherms. The QSDFT model improves significantly the method of adsorption porosimetry: the pore size distribution (PSD) functions do not possess gaps in the regions of ∼1 nm and ∼2 nm, which are typical artifacts of the std. non-local d. functional theory (NLDFT) model that treats the pore walls as homogeneous graphite-like plane surfaces. The advantages of the QSDFT method are demonstrated on various carbons, including activated C fibers, coal based granular C, water purifn. adsorbents, and micro-mesoporous C CMK-1 templated on MCM-48 SiO2. The results of PSD calcns. from N and Ar are consistent, however, Ar adsorption provides a better resoln. of micropore sizes at low vapor pressures than N adsorption. [on SciFinder(R)]
Keywords: carbon adsorbent pore size distribution adsorption isotherm simulation